KINETOSTATIC ANALYSIS OF LINKAGE MECHANISMS TAKING INTO ACCOUNT THE FRICTION IN KINEMATIC PAIRS - Харжевський, В’ячеслав Олександрович; Марченко, Максим Васильович (Problems of Friction and Wear, 2019)
The paper deals with a problem of designing of linkage mechanisms that can be used in various types of machines in different fields of machinery. One of the important parts of mechanisms’ design process is carrying out their kinetostatic analysis in order to find forces in the kinematic pairs of mechanisms. But the kinetostatic analysis of linkages is usually performed without friction considerations, so the development of the numerical and analytical methods to carry out the kinetostatic analysis of linkage mechanisms taking into account the friction in the kinematic pairs is an important task that can be solved using a modular approach. In this paper we consider the second-class linkage mechanisms (at the classification of Assur-Artobolevsky), and it is known that there exist 5 types of structural groups of the II class. Since every mechanism of the second class can be divided into several structural groups of certain types, so for every type of the structural group the general analytical dependencies can be written. It can be used to calculate kinematic and kinetostatic characteristics of every links and points of mechanism. It is established that such calculations can be performed with the friction taken into account by means of consecutive approaching method. So, the algorithms of the kinetostatic analysis of the second-class linkage mechanisms with considering the friction in the kinematic pairs and the appropriate software on their basis have been developed. An optimization procedure using different parameters can be also carried out. Some results of carried calculations are given, in particular the kinetostatic analysis of the sample six-link linkage mechanism.